Review: Zbigniew Dąbrowski, Anna Marchewka, Aneta Teległów (eds.), "Hematologia sportowa" [Sports Haematology], Wydawnictwo Lekarskie PZWL, Warszawa 2022 - Teległów, Aneta (Health Promotion & Physical Activity, 2025)
The academic textbook entitled Hematologia sportowa [Sports Haematology] was published by Wydawnictwo Lekarskie PZWL in Warsaw. It had its premiere on November 23, 2021 and was released in printed form (paperback, 244 pages, ISBN number: 978-83-200-6573-2). The publication was co-financed under the programme of the Minister of Science and Higher Education entitled ‘Regional Initiative of Excellence’ in years 2019–2022, project number 022/RID/2018/19. The handbook is a result or a collaborative effort under the scientific editorship by Prof. Zbigniew Dąbrowski, Prof. Anna Marchewka, and Assoc. Prof. Aneta Teległów (University of Physical Culture in Krakow). The author contributors include 10 academics from the University of Physical Culture in Krakow and 13 academics or physicians representing other research institutions.